The place of knot and exposition in a work of art (L.Borikhon's the example of novel “People in the heat") (Zien Journal of Social Sciences and Humanities, 2024)
This article will talk about the plot construction of samples of fiction created in Uzbek literature. During the analysis, the novel “people in the heat” by the writer Luqmon Boukhon was drawn into a separate analysis. The work talks about the knot and the exposition